Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) pada Pembelajaran IPS Siswa - Pramesti, Adia; Sukasno, Sukasno; Prananosa, Ahmad Gawdy (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the completeness of the social studies learning outcomes of fourth-grade students of SD Negeri 61 Lubuklinggau after the Teams Games Tournament (TGT) Learning Model was implemented. The research method is quantitative research with a Pre-Expremimental Design approach. The population is all fourth-grade students and the sample is fourth-grade students of SD Negeri 61 Lubuklinggau who were taken using random sampling techniques. Data collection was carried out using test techniques, in the from of multiple choices of 14 questions. The data analysis technique used the t-test, with a significance level of a = 0,05. The result of the data analysis can be concluded that the social studies learning outcomes of fourth-grade students of SD Negeri 61 Lubuklinggau after the Teans Games Tournament (TGT) Learning Model was implemented significantly. With an average value of 80,10 and the precentage of students who completed reaching 93%. Keywords: Cooperatif Learning, Contextual Teaching and Learning, Learning Outcomes, Social Studies.